Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I am trying to simplify an expression involving summation as follows:

$$\sum_{i=0}^{n-1} { {2n}\choose{i}}\cdot x^i$$

where $n$ is an integer, and $x$ is a positive real number.

At a first glance, I can see that

$$\sum_{i=0}^{2n} { {2n}\choose{i}}\cdot x^i = {(1+x)}^{2n}.$$

But what if in the case when $i$ goes from 0 to $n-1$?

share|cite|improve this question
up vote 1 down vote accepted

If you sum from $0$ to $n-1$, then no longer you get an easy espression. Instead, you can get the sum in terms of the hypergeometric function

$$ \left( x+1 \right) ^{2\,n}-{2\,n\choose n}{x}^{n} {F (1,-n;\,n+1;\,-x)}\,.$$

share|cite|improve this answer

It's just a partial answer.

Let $S_1(x):=\sum_{i=0}^{n-1}\binom{2n}ix^i$, and $S_2(x):=\sum_{i=n+1}^{2n}\binom{2n}ix^i$. Then writing $j=2n-i$, we get $$S_2(x)=\sum_{j=0}^{n-1}\binom{2n}jx^{2n-j}=S_1(x^{-1})x^{2n}.$$ So $$(1+x)^{2n}=S_1(x)+\binom{2n}nx^n+S_2(x)=S_1(x)+\binom{2n}nx^n+S_1(x^{-1})x^{2n}.$$ Writing $f(x):=\frac{S_1(x)}{x^n}$, we get that $f$ satisfies the functional equation $$f(x)+f(x^{-1})=\left(1+\frac 1x\right)^n(1+x)^n-\binom{2n}n.$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.